The Concept of Human Potentials: Qalb, ‘Aql, Fu’ad, A’yun, and Al-Udzun - Firma, Heldi Firma; Kadar; Alwizar (The Future of Education Journal, 2025)
This study aims to examine the concept of human potentials from the perspective of the Qur’an, specifically those related to qalb, ‘aql, fu’ad, a’yun, and al-uzun. Understanding these potentials forms a crucial foundation in Islamic education, considering that human beings, as subjects of education, are endowed with innate capacities (fitrah) to develop both spiritually and intellectually. Using a literature review approach, this research identifies that each potential has a specific function that supports the perfection of human beings as khalifah (vicegerents) on earth. Qalb functions as the center of inner consciousness, ‘aql as the faculty of reasoning, fu’ad as the core of conviction and inner reflection, a’yun as the visual perception tool essential for learning, and al-uzun as the auditory receptor influencing understanding and internalization of knowledge. This study highlights the importance of developing these potentials within an integrated Islamic educational framework, aiming to nurture individuals who are faithful, knowledgeable, and morally upright.